Libraries & Scribes in Mesopotamia - القطان, شعيب فراس ابراهيم; خليل, علاء ثامر (مجلة دراسات في التاريخ والآثار, 2023)
The Library For the People of Mesopotamia Means That Place Designated for Preserving a Group of clay Tablets , which Include the same Literary, Religious, Historical, Scientific Texts and other Sciences in all Fields and Details of their Daily life, Organized in the Building of the Temple, Palace or Residence, as the Collection of these Tablets can be That Priests, Scribes, Students, or some Individuals who were on the side of Knowledge Benefit from it and The Writer Appeared in Mesopotamian Society Since an Early Period, dating back to the Borders of 3000 BC. Among the class of Priests at the Beginning was an Urgent and Necessary need to meet the Economic Requirements of that Society , The Economic, Administrative, Property, and Religious Requirements of the Community were written down, as there were Schools to Train and Teach Young People Writing at the Time.